A novel technique to repair orbital roof defects: irradiated homologous cadaveric rib (Tutoplast ®) graft in a recurrent frontal sinus ossifying fibroma. Issue 11 (23rd November 2022) - Acharya, Vikas; Ng, Jimmy; Navaratnam, Annakan; Rennie, Catherine; Clarke, Peter
Abstract: Ossifying fibroma in the fronto-ethmoidal sinuses is a rare, benign condition. In symptomatic cases, surgical excision is often undertaken and bony defects may be repaired using alloplastic grafts. We present a novel method of repairing an orbital roof defect using irradiated homologous cadaveric rib (Tutoplast ®) graft, overlaid with a pericranial flap. The patient made an excellent recovery, concluding that it is a viable and safe option with lower morbidity.